2020
DOI: 10.5944/openpraxis.12.4.1124
|View full text |Cite
|
Sign up to set email alerts
|

Tutoring support as a predictor of student retention in distance learning: The case of a University in Ghana

Abstract: The tutor’s role in enhancing student retention in distance learning is paramount. This study aims to predict retention and not actual retention by investigating how tutoring support predicts student retention in distance learning at the University of Cape Coast in Ghana. Moore Transactional Distance Theory underpinned the theoretical framework of this study. The correlational research design was adopted for the study. The multistage sampling technique was used to sample 727 student participants from a samplin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
(27 reference statements)
0
2
0
Order By: Relevance
“…However, in some cases, the use of additional data collection methods may introduce errors in sampling issues and therefore leads to a decrease in the overall prediction accuracy, therefore it is observed that questionnaire data does not improve prediction unless feature selection is performed appropriately [79]. Lastly, twelve (12) studies have opted solely for surveys or questionnaires, and focus group for data collection ( [23], [47], [122], [133], [48], [52], [53], [61], [67], [79], [98], [120]). Moreover, 8 studies have not explicitly discussed the data collection methods.…”
Section: B Dataset Sample Population Size and Collection Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in some cases, the use of additional data collection methods may introduce errors in sampling issues and therefore leads to a decrease in the overall prediction accuracy, therefore it is observed that questionnaire data does not improve prediction unless feature selection is performed appropriately [79]. Lastly, twelve (12) studies have opted solely for surveys or questionnaires, and focus group for data collection ( [23], [47], [122], [133], [48], [52], [53], [61], [67], [79], [98], [120]). Moreover, 8 studies have not explicitly discussed the data collection methods.…”
Section: B Dataset Sample Population Size and Collection Methodsmentioning
confidence: 99%
“…Figure 6 highlights the distribution of the reviewed studies according to the sample population used. While most researchers took student-centred approaches, with nearly half of the studies (47%) focusing on undergraduate students, very few considered the inclusion of educators/teachers in their predictive models, precisely three (3) articles mentioned this [48], [95], [118]. These findings introduce a possible research gap for future researchers to develop a more comprehensive prediction model.…”
Section: B Dataset Sample Population Size and Collection Methodsmentioning
confidence: 99%